The Scientific Buddhism to Improve Human’s Well-Being - et. al., Sitthiporn Khetjoi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This academic article has the purposes to demonstrate and explain about Buddhism as religious of science and the application of science based on Buddhism to improve human’s well-being. The authors studied and collected the data from Buddhist scriptures, texts, and related document about Buddhism and Science to improve human’s well-being, and analyzed by content analysis. The interface between Buddhism and science is the major issue. Scientific method is the answers of natural questions starting from what we understand as the smallest object to largest one by using five steps. It could be summarized into two steps namely rational of mathematic and senses. For Buddhism, Buddhist Philosophy is also interested in two main problems of human namely the problems related to human being directly, or it may be related between human and other human. Buddhist philosophy asserts that it is our minds that contribute most significantly to our own suffering and that the mind can be deconstructed and reconstructed to give the individual a more stable sense of peace, happiness, and equanimity. Also, Buddhism can be seen to have relevance to the commonly defined dimensions of human’s well-being. The four noble truths and the noble eightfold path relate well with sustainability led to well-being. The first and the second o of noble truth explain about causes of suffering and unsustainability whereas the third and the last of the four noble truth explain about the effect or the way of achieving well-being. Wellbeing is stressed in Buddhism supposed to be driven by ethical motivation that seeks to cause no harm to individual and group, to create no agitation in society.